2016
DOI: 10.9790/1959-0504014452
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Poly Cystic Ovarian Disease (PCOD) Among The Girl Students of Bishop Heber College, Trichirapalli, Tamil Nadu, India

Abstract: Polycystic ovarian syndrome (PCOS) is a very common endocrine disorder encountered in womenand is associated with problems, such as menstrual irregularities; hirsuitism; obesity; insulin resistance; acne; and, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Approximately 100% of diagnosed PCOS cases in the conducted survey reported irregularity of menses (p< 0.001) which can be supported by a survey conducted in Tamil Nadu where the student exhibited PCOS induced oligomenorrhea. 13 In addition to this the PCOS afflicted, 88.9% reported acne (p<0.001) and 55.5% reported hirsutism (p<0.01) in the current study. Previous researches have also shed light to such findings where survey conducted in India, showed that 70% students had oligomenorrhea and polycystic ovaries, 13.3% had hirsutism and polycystic ovaries, 3.3% had oligomenorrhea and hirsutism and 13.3% had all the three features.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Approximately 100% of diagnosed PCOS cases in the conducted survey reported irregularity of menses (p< 0.001) which can be supported by a survey conducted in Tamil Nadu where the student exhibited PCOS induced oligomenorrhea. 13 In addition to this the PCOS afflicted, 88.9% reported acne (p<0.001) and 55.5% reported hirsutism (p<0.01) in the current study. Previous researches have also shed light to such findings where survey conducted in India, showed that 70% students had oligomenorrhea and polycystic ovaries, 13.3% had hirsutism and polycystic ovaries, 3.3% had oligomenorrhea and hirsutism and 13.3% had all the three features.…”
Section: Discussionsupporting
confidence: 50%
“…Previous researches have also shed light to such findings where survey conducted in India, showed that 70% students had oligomenorrhea and polycystic ovaries, 13.3% had hirsutism and polycystic ovaries, 3.3% had oligomenorrhea and hirsutism and 13.3% had all the three features. 13 Hirsutism, acne and irregularity of menses can lead to poor self-confidence; thus, precipitating psychological stress. Studies have reported that nearly 50% women in the previous studies and 63.3% (irrespective of whether they were PCO sufferers or not) in the current study significantly (p<0.05 as per likely hood ratio) believed that PCOS is a known cause of infertility and miscarriage which in turn can lead to psychological problems 14 as also evident from the present study where concurrence of depression and occurrence of PCOS as per the knowledge of participants was also significant (p<0.05), though reported by only 22.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation